MON-281 A Pilot Study: Comparing Prolactin Measurements Between Two Different Immunoassays - Woznick, Walter K (J Endocr Soc, 2020)
Hyperprolactinemia from a prolactin-secreting pituitary tumor is the most common endocrine disorder of the hypothalamic-pituitary axis. As suggested in the 2011 Endocrine Society Guidelines on Diagnosis and Treatment of Hyperprolactinemia, macroprolactin level should be assessed in patients with asymptomatic hyperprolactinemia. However, as discussed in prior studies comparing the performance of common prolactin immunoassays in a reference population of both males and females with and without known hyperprolactinemia or macroprolactinemia, there has been poor harmonization between assays and variable reactivity towards macroprolactin, resulting in significantly different normal ranges for total and monomeric prolactin between manufacturers. The goal of our analysis is to assess the concordance of the Roche and Siemens prolactin immunoassays using cases in which prolactin and macroprolactin testing was ordered on clinical indication. We hope to educate clinicians regarding potential variability between assays that may not be fully accounted for by using established, assay-specific reference ranges. We reviewed patients 18 years and older from any gender who underwent evaluation of prolactin levels as clinically indicated and had elevated serum prolactin on a Roche assay with a subsequent normal prolactin on a Siemens assay. Seven out of 18 patients had an elevated prolactin on the Roche assay and a normal prolactin on the subsequent Siemens assay that also tests for the presence of macroprolactin. The reasons for testing prolactin in the 7 patients were: secondary hypogonadism (4), pituitary microadenoma (1), oligomenorrhea (1) and baseline labs in a transgender female starting estrogen (1). Of the 7 cases we observed with discordant Roche and Siemens prolactin results, one of our 2 female patients and one of our 4 male patients would have shown concordant hyperprolactinemia results on both assays if the Siemens reference range was narrowed to align with published studies. This study demonstrates significant analytical discordance between prolactin immunoassays, leading to variable clinical interpretation regarding the presence of hyperprolactinemia. We suggest using a single prolactin immunoassay for routine measurement of prolactin as well as investigation of macroprolactin measurement to ensure comparable reactivity towards all forms of prolactin. References: (1) Vallette-Kasic et al., J Clin Endocrinol Metab. 2002 Feb;87(2):581-8. (2) Gibney et al., J Clin Endocrinol Metab. 2005 Jul;90(7):3927-32. (3) Luisa et al., Clinical chemistry 2008 Sept; 54:10 1673-1681 (4) Shlomo et al., J Clin Endocrinol Metab, February 2011, 96(2):273-288